Endovascular treatment of a giant false aneurism of suprarenal aorta - S. N. Furkalo; I. V. Khasyanova; A. V. Liksunov; D. A. Prysiazhniuk (Клінічна хірургія, 2021)
Endovascular treatment of a giant false aneurism of suprarenal aorta